Analysis of Mathematical Communication of Students Through AIR Model at SMAN 1 Driyorejo Gresik - Safitri, Refanni Nadya; Sulistyaningtyas, Annisa Dwi (Indonesian Journal of Education and Mathematical Science, 2024)
The learning model during the Covid-19 pandemic has reduced students' mathematical communication because students are very dependent on gadget facilities. In this study, researchers used a learning model, namely Cooperative Auditory Intellectually Repetition (AIR). This study aims to determine the effect of Cooperative AIR learning model on students' mathematical communication on the material of System of Linear Equations of Three Variables (SPLTV) at SMAN 1 Driyorejo Gresik. This learning model is a quantitative research with data collection techniques that apply the test process using normality test, homogeneity test, and continued with hypothesis testing. The test instrument used was a post-test on students' mathematical communication as many as two questions. Based on the calculation result of students' mathematical communication test, it was found that students' mathematical communication using Cooperative AIR learning model was better than students' mathematical communication using Cooperative Jigsaw learning model with  or  rejected, so it can be concluded that there is an effect of Cooperative AIR learning model on mathematical communication of class X students at SMAN 1 Driyorejo Gresik on SPLTV material.